"The Starry Sky." A new intraprocedural three‐dimensional echocardiographic technique. Issue 9 (5th September 2019) - Vairo, Alessandro; Marro, Matteo; Speziali, Giovanni; Rinaldi, Mauro; Salizzoni, Stefano
Abstract: The NeoChord procedure is a micro‐invasive, trans‐ventricular, beating‐heart chordal replacement technique for patients with severe degenerative mitral valve regurgitation resulting from prolapsed or flail leaflets. Three dimensional transoesophageal echocardiographic guidance is crucial to assist the operator during the procedure. Equidistant placement of neochordae along the free edge of the prolapsing leaflet segment is important to ensure uniform stress distribution and to avoid damaging any of the previously placed neochordae. Lowering the image gain associated with the three‐dimensional surgical view of the mitral valve allows for signal attenuation of the native structures delineating the precise placement location of the neochordae.